STUDI PEMURNIAN GAMBIR (Uncaria gambir Roxb) DENGAN MENGGUNAKAN ARANG AKTIF DARI TEMPURUNG KELAPA SAWIT SEBAGAI ADSORBEN - Ferdinal, Norman; Nazir, Novizar (Universitas Andalas, 2010)
ABSTRACTThe purpose of this research is to know the effect of particle size and concentration activator MgCl2 to effectiveness the active carbon and examine the ability of the best active carbon that produced as adsorben to purifying gambier. This research is done in 3 steps: (A) the making of the active carbon from variety of size : ≥ 250µm (A1),180µm < F ≤ 250µm (A2), 125µm < F ≤ 80 µm (A3) and F ≤ 125 (A4) and some the activator concentration MgC12 : 0% (B1), 20% (B2), 40% (B3), 60% (B4) and 80% (B5), (B) the testing quality of the active carbon include the content of water and adsorbable Iod and (C) the testing of active carbon as adsorben to purifying of gambier. To examine about the quality of active carbon got the best active carbon from carbon of coconut shell of sawit by size ≤ 125µm with activator concentration 20% MgC12 with the content of water 2.23% and adsorbable Iod 3080.97 (mg/g). The gambir rendemen the best purifying that produced is 55.5% by the content of dust 1.303% and the content of catechin 72.40%. Keywords: Catechin compounds, Active carbon.